Assessment of Water Quality around Selected Dams and Irrigation Projects in Nigeria - Ujoh, Fanan; Dam, Daniel Peverga; Alhassan, Muhammad Mamman (Kashere Journal of Politics and International Relations, 2025)
This study assesses quality of water sources within dams and 4 irrigation project (Gurara Irrigation Project, Bakolori Irrigation Project, Oyan Irrigation Project, and Isampou Irrigation Project) sites located in 4 river basins (Upper Niger, Sokoto-Rima, Ogun-Oshun, and Niger-Delta) across Nigeria. Water samples were collected in each of the 4 different locations and analysed at Kaduna Environmental Protection Authority (KEPA) Laboratory, using Atomic Absorption Spectrometer (AAS) among others, focusing on the concentration levels of key water parameters including physio-chemical, heavy metals, and microbial count. The two-way ANOVA was conducted for the laboratory results of all 7 heavy metals as a basis for understanding the impact of both location and heavy metal type on the concentration of heavy metals in the water. The outcome of the two-way ANOVA analysis reveals that there is no significant difference in the mineral contamination of Cu, Cr, Fe, Mg, Mn and Zn across all 4 locations. Only Ca appears to have recorded a significant divergence in the records from the 4 project sites. The result also reveals EC, Na and K with mean concentration values above permissible limit (APL) for irrigation standards as well as for drinking water set by the WHO (2012). The microbial counts for Total Coliform Count (TCC), Thermo Tolerant Count (TTC) and Bacterial Count in majority of the samples assessed were relatively high. Based on the result, the study recommends periodic water quality monitoring in the study areas with the view to early detections and treatment.